2013
DOI: 10.1158/1078-0432.ccr-12-3295
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Proliferation and Migration by Keratin19-Induced Nuclear Import of Early Growth Response-1 in Breast Cancer Cells

Abstract: Purpose: Keratin19 (KRT19) is the smallest known type I intermediate filament and is used as a marker for reverse transcriptase PCR-mediated detection of disseminated tumors. In this study, we investigated the functional analysis of KRT19 in human breast cancer.Experimental Design: Using a short hairpin RNA system, we silenced KRT19 in breast cancer cells. KRT19 silencing was verified by Western blot analysis and immunocytochemistry. We further examined the effect of KRT19 silencing on breast cancer cells by c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 38 publications
4
65
0
Order By: Relevance
“…We propose that mitogen stimulation of K17-expressing tumor cells results in posttranslational modifications of K17 that increase its nuclear targeting and binding of p27 KIP1 and CRM1, leading to p27 KIP1 export. Previous studies on other keratins reported their role in nuclear localization of Egr1 in breast cancer cells (41) and cytoplasmic retention of 14-3-3s in mouse keratinocytes (42). Therefore, the confirmation that K17 undergoes nuclear translocation casts light on the dynamic role of K17 that extends beyond its role in mechanical support, functioning as a nuclear shuttle for p27 KIP1 and potentially other tumor suppressors and nuclear proteins.…”
Section: Discussionmentioning
confidence: 76%
“…We propose that mitogen stimulation of K17-expressing tumor cells results in posttranslational modifications of K17 that increase its nuclear targeting and binding of p27 KIP1 and CRM1, leading to p27 KIP1 export. Previous studies on other keratins reported their role in nuclear localization of Egr1 in breast cancer cells (41) and cytoplasmic retention of 14-3-3s in mouse keratinocytes (42). Therefore, the confirmation that K17 undergoes nuclear translocation casts light on the dynamic role of K17 that extends beyond its role in mechanical support, functioning as a nuclear shuttle for p27 KIP1 and potentially other tumor suppressors and nuclear proteins.…”
Section: Discussionmentioning
confidence: 76%
“…36 However, it must be noted that complete silencing of KRT19 by shRNA leads to upregulation of cell proliferation by an increase in Akt activity via inhibition of Egr-1/PTEN, as we have reported very recently. 37 As indicated in Supplementary Figure 6, KRT19 exhibited a biphasic effect on cancer cell proliferation. The cell viability was dependent on KRT19/HER2 signaling at higher KRT19 concentration and it turned to be rather dependent on KRT19/Egr-1 signaling at very low/knockout levels of KRT19.…”
Section: Discussionmentioning
confidence: 91%
“…Keratins have been implicated in the modulation of Akt and mTOR signaling pathways through direct physical interaction with the adapter protein 14-3-3σ stratifin) [41], AMP-activated protein kinase (AMPK) [42] and Akt/PKB [43, 44], or via transcriptional regulation of the effector genes in the pathway [14, 45]. Previous studies on the regulation of nociceptive mechanisms show that sensory axonal protein synthesis also occurs under the control of the mTOR signaling pathway [4749].…”
Section: Discussionmentioning
confidence: 99%